Protective Effects of Fucoxanthin on High Glucose- and 4-Hydroxynonenal (4-HNE)-Induced Injury in Human Retinal Pigment Epithelial Cells - Yi-Fen Chiang; Hsin-Yuan Chen; Yen-Jui Chang; Yin-Hwa Shih; Tzong-Ming Shieh; Kai-Lee Wang; Shih-Min Hsia (MDPI AG, 2020)
The incidence of diabetes mellitus is increasing due to the eating and living habits of modern people. As the disease progresses, the long-term effects of diabetes can cause microvascular disease, causing dysfunction in different parts of the body, which, in turn, leads to different complications, such as diabetic neuropathy, diabetic nephropathy, and diabetic retinopathy (DR). DR is the main cause of vision loss and blindness in diabetic patients. Persistent hyperglycemia may cause damage to the retina, induce the accumulation of inflammatory factors, and destroy the blood-retinal barrier function. Fucoxanthin (Fx) is a marine carotenoid extracted from seaweed. It accounts for more than 10% of the total carotenoids in nature. Fx is mainly found in brown algae and has strong antioxidant properties, due to its unique biologically active structure. This carotenoid also has the effects of reducing lipid peroxidation, reducing DNA damage, and preventing cardiovascular diseases as well as anti-inflammatory and anti-tumor effects. However, there is no relevant research on the protective effect of Fx in DR. Therefore, in this study, we explore the protective effect of Fx on the retina. Human retinal epithelial cells (ARPE-19) are used to investigate the protective effect of Fx on high glucose stress- (glucose 75 mM) and high lipid peroxidation stress (4-hydroxynonenal, 4-HNE (30 μM))-induced DR. The cell viability test shows that Fx recovered the cell damage, and Western blotting shows that Fx reduced the inflammation response and maintained the integrity of the blood-retinal barrier by reducing its apoptosis and cell adhesion factor protein expression. Using an antioxidant enzyme assay kit, we find that the protective effect of Fx may be related to the strong antioxidant properties of Fx, which increases catalase and reduces oxidative stress to produce a protective effect on the retina.